Morphological Studies and Identification of DSE Fungi and Their Role in Sustainable Agriculture: A Systematic Review - Aulia, Nabila Nurul; Meiza, Aisyifa Nur; Sari, Indah Juwita; Khastini, Rida Oktorida; Nafsahan, Hurry Khastina (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
The use of endophytic fungi as producers of bioactive compounds is popular among researchers today. One example of endophytic fungi that is currently widely studied regarding its role is DSE fungi. Determining the morphological structure and identification of DSE fungus as well as its function as a sustainable agricultural agent, are the goals of this study. Several scientific papers that are pertinent to the subject matter are gathered, chosen, and reviewed as part of the systematic literature review research methodology. Developing a research question, looking through pertinent literature, choosing studies with eligibility requirements and quality evaluation, and extracting data were the first stages of the study. Based on the data analysis, DSE fungi have the ability to increase plant productivity and resistance to biotic and abiotic stress, as well as their contribution to phytostabilization and nutrient accumulation. In addition, DSE fungi can produce beneficial secondary metabolites, such as growth hormones and bioactive compounds, which support plant health. The use of DSE fungi also has the potential to support plant growth in sustainable agriculture